EFFECTIVENESS OF BODY POSITION ON PAIN, DYSPHAGIA, TEMPOROMANDIBULAR JOINT (TMJ) MOBILITY AND NECK MOBILITY IN POST RADICAL NECK DISSECTION PATIENTS. - Bhije, Pratiksha Abhay; Yadav, Trupti S (South Eastern European Journal of Public Health, 2025)
Anatomic and functional disorders after surgical resection of various head-and-neck cancers have been well documented. Postoperative complications are observed to be caused by decreased swallowing efficiency and temporomandibular joint and cervical joint mobility1,2. Dysphagia and related post-operative complication lead to malnutrition, reduces the quality of life, and cause postural malalignment2. As per the study, alteration of tongue and swallowing muscle properties are associated with different body positions1. The effect of body posturing on pain, dysphagia, temporomandibular joint (TMJ) mobility, and neck mobility in post-radical neck dissection patients is unclear. Aim and Methodology: This study aims to investigate the effectiveness of body position on pain, dysphagia, temporomandibular joint (TMJ) mobility, and neck mobility in post-radical neck dissection patients. The study design was a randomized controlled trial, and the sample size was 40 post-radical neck dissection patients. The intervention group received physiotherapy treatment that included Swallowing exercises with targeted body position, while the control group received standard care containing swallowing exercises alone. The outcome measures was pain, dysphagia, TMJ mobility, and neck mobility, which was assessed using validated scales and measurements. Data was analysed using descriptive statistics and inferential statistics, including t-tests and ANOVA. Results: The study reviewed 40 subjects with head and neck cancer. These included radical neck dissection at surgical levels, II to VII as per inclusion criteria and were assigned into two groups, Scores were lower when swallowing exercises were given without body positioning, and scores were improved when swallowing exercises were given with body positioning (P <0.0001). The results of this study provide valuable information on the effectiveness of physiotherapy treatment in improving pain, dysphagia, TMJ mobility, and neck mobility in post-radical neck dissection patients when the two groups were compared (P<0.05). Conclusion: The present study concludes that swallowing exercises along with Targeted Body Position was beneficial for reducing post operative pain and improving swallowing ability, Temporomandibular joint, and cervical joint mobility in post-radical neck dissection patients.